Evaluation of National Policy about Domestic Violence against Women in Iran - Bahare Fallahi Aida Mehrad (Journal of Educational, Health and Community Psychology, 2014)
Abstract One of the unpleasant behaviors that threats women’ life and leads to various disquiets among family members is domestic violence. Prevention of  this  social dilemma and  recognizing of  its  mechanism supposed as  a  vital  and predictable fact in national policies. Into the bargain, it is enough necessary to determine the national policies for protecting women to meliorate mental health in society. The goal of current literature is looking at the factors that may contribute to domestic violence against women. Also, this paper evaluate position of women in constitute law, civil law and national policies in Iran with the purpose of women’ protect in the society. Key word: Domestic violence, Women, National policy, Iran